Crystal growth, structure, and dielectric properties of layered cobaltates La2−xSrxCoO4 (x = 0.4, 0.5, and 0.6) single crystal. (January 2015) - Dong, S.T.; Sun, N.; Zhang, B.B.; Zhang, F.; Yao, S.H.; Zhou, J.; Zhang, S.T.; Gu, Z.B.; Chen, Y.B.; Chen, Y.F.
Graphical abstract: Highlights: La2− x Sr x CoO4 ( x  = 0.4, 0.5, and 0.6) crystals have been successfully grown by FZ method. The c -axis of as-grown crystals is perpendicular to the growth direction. The origination of giant dielectric constant is the mixed-valence Co 2+ and Co 3+ . The dielectric relaxation shows a thermal-activated behavior. Abstract: In this work, La2− x Sr x CoO4 ( x  = 0.4, 0.5, and 0.6) crystals with the Ruddlesden–Popper K2 NiF4 -type structure have been grown by the floating zone method. This compound crystallizes in the K2 NiF4 -type structure with space group I4/mmm. Temperature-dependent dielectric properties of the as-grown crystals were studied over a broad frequency range. The origin of the giant dielectric constant in this system is the mixed-valence structure between Co 2+ and Co 3+, and the dielectric constant at high frequency is related to the charge ordering structure. The dielectric relaxation shows a thermally-activated behavior. The corresponding activation energy (assigned to small polaronic hopping) can be obtained by Arrhenius fitting.